Daur al-Maḥfūḍāt fī Tanmiyyah Mahārah al-Kalām Laday al-Muta'allimīn fī al-Marḥalah al-'Idādiyyah - Garba, Ahmad (Al-Fusha : Arabic Language Education Journal, 2024)
This paper aims to shed light on the function of memorized materials and its role in developing the speaking skills of a students in junior secondary schools, especially those in the third grade, to achieve this objective, is become necessary to select an appropriate methods, materials to be taught as well as the teacher’s emotional participation with the students, and on this basis, the success or failure of an educational curriculum depends the method of teaching selected, equally, student is also considered the most important factor in the success of the educational process, so methods and student remained its main focus, and these methods of teaching were numerous and differed in their style and characteristics, This paper contains the definition of the memorized materials, it objectives, it teaching methods, it role in developing the speaking skill, the importance of the speaking skill in the preparatory stage, the methods of developing this skill, and the problems that a teacher may face in developing the speaking skill of a student.